Research Note: Creatine monohydrate alleviates protein breakdown induced by corticosterone via inhibiting ubiquitin proteasome pathway in chicken myotubes - Mingfa Sun; Hongchao Jiao; Jingpeng Zhao; Xiaojuan Wang; Haifang Li; Yunlei Zhou; Hai Lin (Poultry Science, 2022)
Stress is a common problem diminishing the muscle development of broilers. Creatine (Cr), an energy buffer in skeletal muscle, plays a fundamental role in muscle physiology. This study aimed to evaluate the effect of Cr monohydrate (CMH) on protein breakdown in chicken myotubes challenged by corticosterone (CORT) in vitro. The morphology of myotube was measured and the activation of ubiquitin proteasome (UP) pathway was determined. The result showed that CORT treatment decreased myotube diameter (P < 0.05), increased 3-methyl-histidine (3M-His) content in medium, enhanced the mRNA expression levels of muscle ring finger1 (MuRF1) and Atrogin1 (P < 0.001), and Atrogin1 protein level (P < 0.05) compared with control. By contrast, CMH increased myotube diameter (P < 0.05) and myosin heavy chain (MHC) expression (P < 0.001), whereas decreased 3M-His and the mRNA and protein levels of Atrogin1 (P < 0.05), compared to control. In the present of CMH, the decreased myotube diameter and increased 3M-His, mRNA levels of MuRF1 and Atrogin1, and Atrogin1 protein level by CORT were partially relieved (P < 0.05). Hence, the result suggests that CMH alleviates CORT-induced protein breakdown by suppressing Atrogin1 expression in chicken myotubes. The result highlights the potential application of CMH in regulating muscle protein catabolism in chickens under stress.